Effects of sleep deprivation on sports performance and perceived exertion in athletes and non-athletes: a systematic review and meta-analysis - Kong, Y.; Yu, B.; Guan, G.; Wang, Y.; He, H. (Frontiers in Physiology, 2025)
Background: Sleep deprivation can significantly affect sports performance and the perception of fatigue. However, the impact of sleep deprivation on sports performance remains a subject of ongoing debate across different populations.